Early cytotoxic lymphocyte expansion contributes to a deep molecular response to dasatinib in patients with newly diagnosed chronic myeloid leukemia in the chronic phase: results of the D‐first study. Issue 9 (September 2015) - Iriyama, Noriyoshi; Fujisawa, Shin; Yoshida, Chikashi; Wakita, Hisashi; Chiba, Shigeru; Okamoto, Shinichiro; Kawakami, Kimihiro; Takezako, Naoki; Kumagai, Takashi; Inokuchi, Koiti; Ohyashiki, Kazuma; Taguchi, Jun; et al.
<x xml:space="preserve">Abstract</x> Dasatinib is one of the key treatment options for chronic myeloid leukemia (CML) patients. Increase in lymphocyte counts has been known to be predictive of a good treatment response under dasatinib treatment as a second line therapy. However, clinical significance of lymphocyte dynamics in the upfront setting has yet to be clarified. To investigate the significance of lymphocyte dynamics in newly diagnosed chronic phase (CP)‐CML, patient data of D‐First study (ClinicalTrials.gov NCT01464411) were analyzed. Fifty‐two CML‐CP patients enrolled to this study were treated with dasatinib (100 mg day−1) and all were followed‐up for 18 months. The incidence of lymphocyosis was observed in 14 (27%), but it was not associated with deep molecular response achievement. However, natural killer (NK) cell or cytotoxic T lymphocyte (CTL) counts at 1 month were significantly higher in patients with deep molecular response (DMR) by 18 months compared to those without DMR. When the patients were divided into two groups according to those calculated thresholds by receiver operating characteristic curve (407/μL for NK cells and 347/μL for CTLs), the cumulative DMR rates by 18 months were significantly better in higher value group compared to lower value group. In contrast, regulatory T cell counts were significantly lower at 12 and 15 months in patients achieved DMR. These results suggest the presence of dual effects of dasatinib on immune system through the cytotoxic lymphocytes activation and Treg deregulation in different periods in newly diagnosed CML‐CP. Am. J. Hematol. 90:819–824, 2015. © 2015 Wiley Periodicals, Inc.